Is the Simultaneous Verbal Protocol a Viable Method for Studying Managerial Problem Solving and Decision Making? - Schweiger, David M. (Academy of Management Journal, 1983)
The article assesses the impact of the simultaneous verbal protocol on problem solving and decision making performance for a complex managerial task. The author believes there has been an increasing focus by management and decision researchers in examining managerial problem solving and decision making, but it is still not well known. Fourty graduate business students engaged in a computer-simulation management game that required they make 17 decisions per period. The study entailed ten decision periods. Performance was measured by operating profit, return on assets, and market share. The study found little difference between those that used simultaneous verbal protocols and those that did not.